The Wari Civilization and Their Descendants: Imperial Transformation in Pre-Inca Cuzco - Glowacki, Mary; McEwan, Gordon Francis (Lexington Books, 2021)
"Drawing on research conducted in Cuzco, Peru, The Wari Civilization and Their Descendants: Imperial Transformation in Pre-Inca Cuzco analyzes the political and social transformations that led to the downfall of the Wari civilization in the Andean Middle Horizon period (AD 500-1000) and resulted in the rise of the Inca state."--
Keywords: Antiquities; Antiquities; Excavations (Archaeology); Cusco (Region); Indians of South America; Cusco (Region); Pikillacta Site (Peru); Cusco (Peru : Region); Cuzco; History; Huari pottery; Huari Indians; Peru; Politics and government; Huari Indians; dept.ant; faculty_collection

Health, Diet, and Violence during Wari Expansion: Bioarchaeology at Ak’awillay, Cusco, Peru - Bey, Bridget C.; Andrushko, Valerie A.; Bélisle, Véronique (Ñawpa Pacha, 2021)
The expansion of states and empires often has important consequences for local populations, including increased violence, greater stress, or dietary modifications resulting in changing health conditions. This paper presents the analysis of 73 skeletons from the Cusco site of Ak’awillay, shedding light on diet, health, and violence in the Middle Horizon. Results indicate that the people of Ak’awillay led a rigorous lifestyle and suffered from more nutritional deficiencies compared to previous populations, possibly pointing to increased maize consumption. However, the low incidence of trauma at Ak’awillay and other Cusco sites suggest that the Wari presence in Cusco was not entrenched in violence.
Keywords: Horizonte Medio; Human remains; Middle Horizon; Wari; burials; dept.ant; diet; dieta; entierros; health; peer-reviewed; restos humanos; salud; violence; violencia

Canine sexual dimorphism in Ardipithecus ramidus was nearly human-like. - Suwa; Sasaki, Tomohiko; Semaw, Sileshi; Rogers, Michael J.; Simpson, Scott W.; Kunimatsu, Yutaka; Nakatsukasa, Masato; Kono, Reiko T.; Zhang, Yingqi; Beyene, Yonas; Asfaw, Berhane; White, Tim D. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Body and canine size dimorphism in fossils inform sociobehavioral hypotheses on human evolution and have been of interest since Darwin’s famous reflections on the subject. Here, we assemble a large dataset of fossil canines of the human clade, including all available Ardipithecus ramidus fossils recovered from the Middle Awash and Gona research areas in Ethiopia, and systematically examine canine dimorphism through evolutionary time. In particular, we apply a Bayesian probabilistic method that reduces bias when estimating weak and moderate levels of dimorphism. Our results show that Ar. ramidus canine dimorphism was significantly weaker than in the bonobo, the least dimorphic and behaviorally least aggressive among extant great apes. Average male-to-female size ratios of the canine in Ar. ramidus are estimated as 1.06 and 1.13 in the upper and lower canines, respectively, within modern human population ranges of variation. The slightly greater magnitude of canine size dimorphism in the lower than in the upper canines of Ar. ramidus appears to be shared with early Australopithecus, suggesting that male canine reduction was initially more advanced in the behaviorally important upper canine. The available fossil evidence suggests a drastic size reduction of the male canine prior to Ar. ramidus and the earliest known members of the human clade, with little change in canine dimorphism levels thereafter. This evolutionary pattern indicates a profound behavioral shift associated with comparatively weak levels of male aggression early in human evolution, a pattern that was subsequently shared by Australopithecus and Homo. © 2021 National Academy of Sciences. All rights reserved.
Keywords: Animals; Australopithecus; Bayes Theorem; Bayes theorem; Biological Evolution; Cuspid; Ethiopia; Female; Fossils; Hominidae; Humans; Male; Models; Pan paniscus; Phylogeny; Sex Characteristics; Theoretical; adult; aggression; anatomy and histology; animal; article; canine tooth; cladistics; classification; dept.ant; evolution; female; fossil; hominid; human; male; mandibular canine; maxillary canine; nonhuman; peer-reviewed; phylogeny; sex difference; sexual characteristics; theoretical model

Estimating sexual size dimorphism in fossil species from posterior probability densities - Sasaki, Tomohiko; Semaw, Sileshi; Rogers, Michael J.; Simpson, Scott W.; Beyene, Yonas; Asfaw, Berhane; White, Tim D.; Suwa (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Accurate characterization of sexual dimorphism is crucial in evolutionary biology because of its significance in understanding present and past adaptations involving reproductive and resource use strategies of species. However, inferring dimorphism in fossil assemblages is difficult, particularly with relatively low dimorphism. Commonly used methods of estimating dimorphism levels in fossils include the mean method, the binomial dimorphism index, and the coefficient of variation method. These methods have been reported to overestimate low levels of dimorphism, which is problematic when investigating issues such as canine size dimorphism in primates and its relation to reproductive strategies. Here, we introduce the posterior density peak (pdPeak) method that utilizes the Bayesian inference to provide posterior probability densities of dimorphism levels and within-sex variance. The highest posterior density point is termed the pdPeak. We investigated performance of the pdPeak method and made comparisons with the above-mentioned conventional methods via 1) computergenerated samples simulating a range of conditions and 2) application to canine crown-diameter datasets of extant known-sex anthropoids. Results showed that the pdPeak method is capable of unbiased estimates in a broader range of dimorphism levels than the other methods and uniquely provides reliable interval estimates. Although attention is required to its underestimation tendency when some of the distributional assumptions are violated, we demonstrate that the pdPeak method enables a more accurate dimorphism estimate at lower dimorphism levels than previously possible, which is important to illuminating human evolution. © 2021 National Academy of Sciences. All rights reserved.
Keywords: Animals; Bayes Theorem; Bayes theorem; Cuspid; Female; Fossils; Male; Models; Sex Characteristics; Statistical; animal; article; attention; canine tooth; controlled study; dept.ant; female; fossil; human; human experiment; intermethod comparison; male; nonhuman; peer-reviewed; primate; probability; sex difference; sexual characteristics; statistical model

Health in the Inca heartland: A paleopathological analysis of burials from the Cuzco region of Peru - Andrushko, Valerie A. (International Journal of Osteoarchaeology, 2021)
While much is known about the rise and expansion of the Inca Empire (AD 1438–1532) throughout the Andean region of South America, the health effects of the empire in its capital region remain unclear. The present study addresses the Inca Empire's impact on health in the Cuzco region of Peru through an analysis of four conditions (dental enamel hypoplasias, cribra orbitalia, porotic hyperostosis and periosteal lesions) in 929 pre-Inca and Inca burials. The study results show little change in health from the Late Intermediate Period (AD 1000–1438) to the Inca Imperial Period (AD 1438–1532). When the location of the Inca burial sites was analysed, individuals from sites closest to the centre of the empire's capital showed lower frequencies in pathological conditions compared with individuals from sites in the countryside. These results suggest that individuals centred in the Inca imperial sphere benefited from their position and experienced better health. A similar finding was also seen with the previous Wari occupation of Cuzco in the Middle Horizon (AD 600–1000), as burials within the Wari imperial sphere exhibited fewer non-specific stress indicators than those outside of it. Overall, the frequencies of pathological conditions in the Cuzco region, which ranged from 4.6% for porotic hyperostosis to 18.8% for periosteal lesions, were lower than frequencies from many coastal Peruvian sites. These differences may relate to a diverse diet provided by the Cuzco region ecosystem, as well as the absence of ecological challenges that affected coastal populations. © 2021 John Wiley & Sons, Ltd.
Keywords: dept.ant; peer-reviewed

Hybrid methods for locating and excavating early historical conflict-related domestic sites - Farley, William A.; McBride, Kevin A.; Willison, Megan K. (Historical Archaeology, 2021)
Since 2012, the Mashantucket Pequot Museum and Research Center in Mashantucket, Connecticut, in collaboration with the University of Connecticut, has carried out a research program to survey and document the battlefields of the Pequot War (1636–1637). The unique nature of the project has required the refinement of the long-standing field methods of battlefield archaeology. In this article, we argue that these techniques, while originally developed to explore sites of conflict, can be operationalized to locate 17th-century indigenous domestic sites. We describe this modified method and provide a site-specific case study to present its efficacy. © 2021, Society for Historical Archaeology.
Keywords: dept.ant; peer-reviewed

Revelations of ancient head shape: Cranial modification in the Cuzco region of Peru, Early Horizon to Inca Imperial Period - Andrushko, V.A. (American Journal of Physical Anthropology, 2021)
Objectives: Cranial vault modification (CVM), the intentional reshaping of the head, indicated group affiliation in prehistoric Andean South America. This study aims to analyze CVM data from the Cuzco region of Peru to illuminate patterns of early migration and settlement along with the later impact of the Inca Empire (AD 1438–1532) on the ethnic landscape. Materials and Methods: 419 individuals from 10 archaeological sites spanning over 2300 years were assessed for CVM using morphological analysis. Results: CVM patterns show distinct temporal attributes: the tabular type of modification appeared first and dominated the early sample (900 BC–AD 600), followed by an influx of unmodified crania during the Middle Horizon (AD 600–1000). The annular type appeared later during the Late Intermediate Period (AD 1000–1438). In the subsequent period of Inca imperialism, modification rates were higher at sites in the Cuzco countryside than in Cuzco city sites. Discussion: The study results, combined with archaeological and ethnohistoric data, reveal the sociopolitical transformations that occurred prior to and during the rise of the Inca Empire. The influx of unmodified crania during the Middle Horizon resulted at least partly from Wari occupation, while the appearance of the annular type during the LIP points to migration into the area, possibly from the Lake Titicaca region. In the Inca Imperial Period, Inca individuals at Cuzco city sites refrained from modification as a sign of their ethnic identity, while modification patterns in the Cuzco countryside likely reflect state-coerced resettlement of different ethnic groups. © 2020 Wiley Periodicals LLC.
Keywords: 15th Century; American Indian; Ancient; Archaeology; Body Modification; Female; History; Human Migration; Humans; Indians; Male; Medieval; Non-Therapeutic; Peru; Skull; South American; adult; archeology; article; body modification; controlled study; dept.ant; ethnic group; ethnology; female; history; human; human experiment; major clinical study; male; migration; occupation; pathology; peer-reviewed; skull